Baoyuan Jiedu decoction alleviating cancer cachexia–Induced muscle atrophy by regulating muscle mitochondrial function in ApcMin/+ mice - Zhang, Beiying; Bi, Qianyu; Huang, Shengqi; Lv, Siyuan; Zong, Xin; Wang, Mengran; Ji, Xuming (Frontiers in Pharmacology, 2022)
Cancer cachexia is a complex syndrome that leads to an ongoing loss of skeletal muscle mass in many malignant tumors. Our previous studies have evaluated the effectiveness of Baoyuan Jiedu decoction (BJD) in alleviating cancer-induced muscle atrophy. However, the mechanisms of BJD regulating muscle atrophy could not be fully understood. Therefore, we further investigated the mechanisms of BJD mitigating muscle atrophy both in an ApcMin/+ mouse model, and the Lewis-conditioned medium induced C2C12 myotube atrophy model. The body weight loss and grip strength of mice were measured. And the gastrocnemius muscle was stained by HE. Transcriptome analysis was applied to investigate the potential mechanisms. ATP content in the gastrocnemius muscle was determined by the colorimetric method and the mitochondrial morphology was observed by electron microscopy. The expression of mtDNA was evaluated by qPCR. Related mRNA and protein expressions were assessed by qPCR and western blot. And the factors reflecting oxidative stress were detected by ELISA. As a result , body weight loss and muscle atrophy were alleviated with BJD treatment. GO analysis suggested that ATP metabolism and mitochondria were involved. The results of the electron microscope show that BJD treatment may have a recovering effect on mitochondrial structure. Besides, ATP content, mitochondrial content, and disrupting mitochondrial membrane potential were improved with BJD treatment. Furthermore, both in vivo and in vitro, we demonstrated that the BJD treatment could improve mitochondrial function owing to the increased number of mitochondria, balanced dynamic, and regulation of the electron transport chain according to the protein and mRNA expressions. In addition, oxidative stress caused by mitochondrial dysfunction was ameliorated by BJD treatment. Consequently, our study provides proof for BJD treatment alleviating cancer cachexia-induced muscle atrophy by modulating mitochondrial function in ApcMin/+ mice.